Desmosterol: A natural product derived from macroalgae modulates inflammatory response and oxidative stress pathways in intestinal epithelial cells - Qu, Huan; Zong, Qiufang; Hu, Ping; Li, Zhaojian; Wang, Haifei; Wu, Shenglong; Liu, Hao-Yu; Bao, Wenbin; Cai, Demin (Frontiers in Immunology, 2023)
The serum level of cholesterol and its biosynthetic intermediates are critical indicators to access metabolism-related disorders in humans and animals. However, the molecular actions of these intermediates on gene functions and regulation remained elusive. Here, we show that desmosterol (DES) is the most abundant intermediate involved in cholesterol biosynthesis and is highly enriched in red/brown algae. It exerts a pivotal role in modulating core genes involved in oxidative stress and inflammatory response processes in the ileum epithelial cells (IPI-2I). We observed that the DES extracted from red algae did not affect IPI-2I cell growth or survival. A transcriptomic measurement revealed that the genes enrolled in the oxidative process and cholesterol homeostasis pathway were significantly down-regulated by DES treatment. Consistent with this notion, cellular reactive oxygen species (ROS) levels were markedly decreased in response to DES treatment. In contrast, key inflammatory genes including IL-6, TNF-α, and IFN-γ were remarkably upregulated in the RNA-seq analysis, as further confirmed by qRT-PCR. Given that DES is a specific agonist of nuclear receptor RORγ, we also found that DES caused the elevated expression of RORγ at mRNA and protein levels, suggesting it is a potential mediator under DES administration. Together, these results underscore the vital physiological actions of DES in inflammatory and oxidative processes possibly via RORγ, and may be helpful in anti-oxidation treatment and immunotherapy in the future.